A straightforward x-ray on applying the ecolabel to the hotel business area - Nicolae Lupu; Mihail Ovidiu Tanase; Remus-Alexandru Tontoroiu (Amfiteatru Economic Journal, 2013)
The ecolabel is a voluntary European initiative for certifying products and services. This study focuses on identifying the perception of persons benefiting of hotel services by designing a research and applying it to the clients of a hotel that acquired the license to use the ecolabel. Identifying the reaction of clients to the ecolabel and the manner it influences the purchase behavior as part of the objectives pursued, were implemented by drafting and applying a questionnaire to the clients of that hotel. Processing the acquired responses was made by the specific applications for data processing, the results confirming only in part the initial assumptions. At a general level, most clients believe that acquiring the ecolabel should be seen in prices, but most of them are unwilling to pay extra for hotel services holding this certificate. Considering that only three accommodation facilities hold this certification in Romania, the research we initiated can be the starting point for developing other more detailed studies concerning the opinion, reasons and purchase behavior of the clients.
Keywords: D12; M14; Q50; 330; ecolabel; sustainable development; hotel management